Comparative evaluation of aerial lime mortars for architectural conservation - Faria, Paulina (2008)
International bibliography on conservation usually refers that mortars made with lime putty with long extinction periods behave better than others made with the current dry hydrated limes. In order to evaluate this assess, an experimental study of lime mortars was carried out, using dry hydrated lime and two lime putties. It becomes clear that the use of lime putties with long extinction periods in mortars allow better performances, particularly in applicability and resistance to sulphates.